Design and development of micro direct methanol fuel cell (μDMFC) for portable application - N. Hashim; S.K. Kamarudin; W.R.W. Daud (Universiti Kebangsaan Malaysia, 2010)
A passive, air-breathing single cell and a multi-cell stack micro direct methanol fuel cell with 1.0 cm2 active area were designed, fabricated and tested. The fuel cell was completely passive without any ancillary device such as pump. Oxygen was taken from the surrounding air, and the methanol solution was stored in a built-in reservoir. The performance of the single cell was tested with different methanol concentrations ranging from 1.0 M to 5.0 M, and the optimum performance was achieved by using methanol at a concentration of 4.0 M. A stack with 6 cells was fabricated and tested with the optimum methanol concentration of 4.0 M, and power levels produced by different catalyst loadings on the anode were compared. The combination of a catalyst loading of 3.0 mg cm-2 Pt/Ru on the anode and 2.0 mg cm-2 Pt on the cathode yielded the highest power of 12.05 mW at 1.08 V and 11.2 mA.